Isolation of a novel manganese-oxidizing bacterium Lysinibacillus xylanilyticus M125: characterization, structural evolution, and Cd-adsorption activity of biogenic Mn oxides produced by the strain - Li, Xiaoju; Yuan, Xinyi; Wei, Yuxia; He, Lianqi; Li, Yuanyuan; Qiu, Meiquan; Liu, Yang; Dong, Nannan; Zhang, Chengjia; Pang, Xin (Frontiers in Microbiology, 2025)
IntroductionManganese-oxidizing bacteria (MOB) play a critical role in converting soluble Mn(II) to insoluble Mn(III/IV) oxides, which have been widely applied for environmental remediation, particularly in heavy metal pollution control. Therefore, the discovery of novel MOB strains is of great significance for advancing pollution mitigation and ecosystem restoration.MethodsIn this study, a manganese-oxidizing bacterial strain was isolated from Mn-contaminated soil near an electroplating factory using selective LB medium supplemented with 10 mmol/L manganese chloride (MnCl2), and the Leucoberbelin Blue (LBB) assay was employed to screen and identify strains with strong Mn(II)-oxidation ability. The isolated strain was identified based on colony morphology, Gram staining, cellular morphology, physio-biochemical analysis, 16S rRNA sequencing, and phylogenetic analysis. The Mn-oxidation ability of this strain was determined by the LBB method. The effects of different pH, temperature, and Mn2+ concentrations on bacterial growth and Mn2+ oxidation were evaluated by OD600nm and LBB method. The biogenic manganese oxides (BioMnOx) produced by strain M125 were characterized using TEM, XRD, XPS, and FTIR analyses. The cadmium adsorption capacity of BioMnOx was assessed using inductively coupled plasma mass spectrometry.ResultsA novel manganese-oxidizing bacterial strain was isolated from Mn-contaminated soil near an electroplating factory and identified as Lysinibacillus xylanilyticus M125. Evaluation of the influence of different pH, temperature, and Mn2+ concentrations on the growth of strain M125 showed that it grew well within a pH range of 5.0–10.0 and a temperature range of 15°C–40°C. It can tolerate Mn2+ concentrations up to 60 mM, indicating strong environmental resilience and potential for practical application. The manganese-oxidizing capacity of strain M125 was significantly affected by both Mn2+ concentration and pH. The oxidation activity increased with Mn2+ concentration up to 12 mM but declined at higher concentrations. Additionally, the strain demonstrated enhanced Mn-oxidation capability under higher pH conditions. BioMnOx, the product of strain M125 oxidation of manganese, had a relatively complex structure, containing a mixture of amorphous MnO2 and crystalline Mn3O4 phase. BioMnOx exhibited various morphologies, including nanosheets, globular structures encased in sheaths, and extracellularly dispersed forms. Long-term cultivation further elucidated the morphological evolution of these oxides. Given the high surface area and porous nature of BioMnOx, its capacity for cadmium adsorption was also assessed. Over 99.5% of cadmium ions in water are adsorbed and removed by strain M125, highlighting its potential for cadmium pollution remediation.DiscussionOverall, this work introduces a new bacterial resource for Mn and Cd bioremediation and offers detailed insights into the structural and functional characteristics of BioMnOx, supporting its application in environmental biotechnology.